Unraveling the Mysteries of Type-A Aortic Dissection Using POCUS/Echocardiography - Syeda Rukh; Sathyanarayana Machani; Milind Awale (Internal Medicine, 2024)
Introduction Acute aortic syndrome (AAS), encompassing aortic dissection (AD), intramural hematoma (IMH), and penetrating aortic ulcer (PAU) occurs at an annual incidence of 50-150 cases per million, with AD comprising 80%, IMH 15%, and PAU five percent. Diagnosis relies on computed tomography (CT), despite limitations. Timely identification is critical due to the high mortality rate of AD, with nearly 40% resulting in immediate death and a subsequent 1-2% increase per untreated hour. Point-of-care ultrasound (POCUS) is emerging as an efficient tool for AD management. Patient Description A 70-year-old male presented to the emergency department (ED) with sudden-onset chest pain, radiating to the ears bilaterally, diaphoresis, and a globus sensation. Vital signs revealed elevated blood pressure. Findings An electrocardiogram (EKG) revealed inferolateral T-wave inversions, prompting a cardiology consultation for suspected acute coronary syndrome (ACS). Nitroglycerin and heparin drips were initiated. Troponins and chest X-rays (CXR) were unremarkable. A bedside transthoracic echocardiogram (TTE) revealed aortic dilation and a false lumen, facilitating diagnosis. Computed tomography angiography (CTA) showed type-A AD. Treatment An esmolol drip was started, followed by urgent surgical transfer. Conclusion AD presents with acute symptoms, often mistaken for a myocardial infarction (MI). POCUS offers bedside execution and aids in hemodynamically unstable patient management. TTE can be done using POCUS. A dilated aortic root (>4 centimeters, cm) strongly suggests AD, while an intimal flap is diagnostic. Cardiac surgery should be consulted upon this finding, as they may opt to forego CT and proceed directly to the operating room. POCUS streamlines patient management, facilitates early specialist consultations, and potentially reduces morbidity and mortality.